The biology of flesh fly, Boettcherisca peregrina (Robineau-Desvoidy, 1830) (Diptera: Sarcophagidae) (Bangladesh Journal of Zoology, 2013)
The biology of Boettcherisca peregrina (Robineau-Desvoidy, 1830) (Diptera: Sarcophagidae) was studied in the laboratory (25 ± 5ºC, R.H. 70 ± 10% and 12 h light: 12 h dark cycle ). There were four definite life stages, such as egg, larva, pupa and adult, in its life cycle. The mean duration of the life cycle was 13.19 ± 1.32 days. The egg was creamy white color, cylindrical, rounded at both ends. The egg shell was comparatively thick and hard. There were three larval instars. The larvae of B. peregrina were acephalous and apodus type. The transparent 12 segmented larva possessed a pair of mouth hook, bands of small backwardly directed black micro spines, a pair of prothorasic spiracle and a pair of posterior spiracle. The 1st larvae were relatively more transparent at the time of hatching. The second instar larvae were voracious feeder. The body size increased largely during the third instar. They were deep creamy to pale brownish in color. The pupae of B. peregrina were coarctate adecticous type. The posterior end of the puparium was rounded and the anterior end was slightly pointed. The adults were metallic brown in color. The males were smaller in size than the females. The mean incubation period was 11.6 ± 2.70 hours, and the larval, post-feeding and pupal periods were 102.22 ± 7.85 hours, 75.4 ± 3.57 hours, and 5.81 ± 1.30 days, respectively. The longevity of the mated male and female adults (36.9 ± 2.46 days and 27.2 ± 2.25 days, respectively) were more than that of the unmated ones (23.6 ± 2.25 days and 18.3 ± 1.5 days, respectively). The protein fed adults lived longer than the protein unfed ones.The male always lived longer than the female. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14312 Bangladesh J. Zool. 40(2): 189-196, 2012